2009
DOI: 10.1074/jbc.m109.030015
|View full text |Cite
|
Sign up to set email alerts
|

Gga2 Mediates Sequential Ubiquitin-independent and Ubiquitin-dependent Steps in the Trafficking of ARN1 from the trans-Golgi Network to the Vacuole

Abstract: In Saccharomyces cerevisiae, ARN1 encodes a transporter for the uptake of ferrichrome, an important nutritional source of iron. In the absence of ferrichrome, Arn1p is sorted directly from the trans-Golgi network (TGN) to the vacuolar lumen via the vacuolar protein-sorting pathway. Arn1p is mis-sorted to the plasma membrane in cells lacking Gga2p, a monomeric clathrin-adaptor protein involved in vesicular transport from the TGN. Although Ggas have been characterized as ubiquitin receptors, we show here that ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 53 publications
2
44
0
10
Order By: Relevance
“…In addition, several studies suggest that sorting of the polytopic membrane proteins Gap1p, Fur4p, Sit1p, and Arn1p involves interaction of covalently bound ubiquitin with the GAT domains of the Gga proteins Scott et al, 2004;Kim et al, 2007), leading to the notion that yeast Ggas might exclusively mediate sorting of ubiquitin-modified cargo. Recent work, however, suggested that TGN-PVC trafficking of Arn1p and Gap1p, albeit Gga dependent, is independent of both ubiquitin modification and the Gga GAT domain, although the mechanism is unknown (Deng et al, 2009;Lauwers et al, 2009). Although the C-tails of both Kex2p and Vps10p are highly acidic, they contain no obvious acidic dileucine motifs.…”
Section: Identification Of the Gga-binding Site In The Kex2p C-tailmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies suggest that sorting of the polytopic membrane proteins Gap1p, Fur4p, Sit1p, and Arn1p involves interaction of covalently bound ubiquitin with the GAT domains of the Gga proteins Scott et al, 2004;Kim et al, 2007), leading to the notion that yeast Ggas might exclusively mediate sorting of ubiquitin-modified cargo. Recent work, however, suggested that TGN-PVC trafficking of Arn1p and Gap1p, albeit Gga dependent, is independent of both ubiquitin modification and the Gga GAT domain, although the mechanism is unknown (Deng et al, 2009;Lauwers et al, 2009). Although the C-tails of both Kex2p and Vps10p are highly acidic, they contain no obvious acidic dileucine motifs.…”
Section: Identification Of the Gga-binding Site In The Kex2p C-tailmentioning
confidence: 99%
“…Recent evidence suggests that the ubiquitin-GAT interaction may be required only for Gga-dependent sorting at the PVC into the luminal vesicles of multivesicular endosomes and that other interactions mediate Gga-dependent sorting of polytopic proteins at the TGN (Deng et al, 2009;Lauwers et al, 2009). Whether the ubiquitin-independent interactions at the TGN involve direct binding to the Gga VHS domains remains to be seen.…”
Section: Interactions Between Gbss In the Kex2p And Vps10p C-tails Anmentioning
confidence: 99%
“…Fractions were collected and subjected to SDS-PAGE and Western blotting using peroxidase anti-peroxidase, anti-GFP (Roche Applied Science) at 1:1000, and anti-Dpm1 (Molecular Probes) at 1:1000. Immunoprecipitations from 55 Fe-labeled cells were performed as described (27) using IgG-Sepharose beads (Sigma). Immune complexes were washed, and 10% of the total washed beads were used for Western blotting, whereas the remainder was subjected to scintillation counting.…”
Section: Methodsmentioning
confidence: 99%
“…dGGA can suppress the defect in the vacuolar protein sorting of yeast gga1gga2 double disruptant In yeast, Gga proteins have been well characterized and are known to play important roles in sorting of membrane proteins in the TGNto-endosomes routes (Hirst et al, 2000;Dell'Angelica et al, 2000;Black and Pelham, 2000;Costaguta et al, 2001;Scott et al, 2004;Deng et al, 2009). The yeast mutant lacking both GGA genes is defective in both sorting of vacuolar soluble proteins such as CPY and processing of mating pheromones (Hirst et al, 2000;Dell'Angelica et al, 2000;Black and Pelham, 2000;Costaguta et al, 2001).…”
Section: Involvement Of Dgga In Lerp Traffic In Vivomentioning
confidence: 99%
“…In the Gga-deficient cells, missorting of vacuolar proteinases such as carboxypeptidase Y (CPY) to the extracellular space occurs due to a defect in the transport of the sorting receptor Vps10p that shuttles between the TGN and endosomes (Hirst et al, 2000;Dell'Angelica et al, 2000). The yeast Ggas are also involved in the Golgi-to-vacuole trafficking of ubiquitylated cargo molecules, such as the Gap1 and Fur4 permeases and of the ferrichrome transporter Arn1p, at the transport step of these membrane proteins into the internal vesicles of multivesicular bodies (MVB) (Scott et al, 2004;Deng et al, 2009;Lauwers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%